Impact of Temperature Variation on Biodiesel Yield and Biodiesel Quality from Waste Cooking Oil Catalyzed by Sulfonated Rubber Seed Shell Activated Carbon - Meiyola, Nada Karima; Suryadri, Hadistya; Heraningsih , Sarah Fiebrina (Jurnal Bio-Geo Material Dan Energi, 2026)
The energy crisis and environmental issues have increased interest in biodiesel as a sustainable fuel. This study examined the effect of reaction temperatures, namely 50°C, 55°C, 60°C, 65°C, and 70°C on the yield and quality of biodiesel produced from a simultaneous esterification transesterification reaction using a 2 %wt catalyst and a mass ratio of methanol to oil, 9:1 for 1 hour. The results showed that temperature has a crucial role in the yield and quality of the resulting biodiesel. The highest yield is 72.62%, was achieved at a temperature of 65°C, producing biodiesel that suitable to SNI 7182:2015 with a density of 875.60 kg/m³, a viscosity of 2.86 cSt, and an acid number of 0.0065 mg-KOH/g. Temperatures above 65°C decreased the yield and quality due to methanol evaporation and incomplete conversion.